Propriedades físicas de nitossolo e latossolos argilosos sob plantio direto - Marcolin, Clovis Dalri (2006)
The soil physical properties and features of a soil play a crucial role in soil management. Texture and organic matter can affect chemical, physical, and biological properties. The aim of the present study was to assess the physical, hydraulic, and mechanical properties of soils with different textures managed under the no-tillage system for ten years in rural estates in the region of Passo Fundo, state of Rio Grande do Sul, in southern Brazil. Samples were collected from five soils at a maximum depth of 30 cm, in six layers. The following parameters were analyzed: texture, soil density, maximum bulk density, optimal moisture content, liquid and plastic limits, ratio between optimal moisture content and plastic limit, water retention curve, organic matter, porosity, mechanical resistance to penetration, relative density, and least limiting water range (LLWR). Organic matter in no-tillage soils is mostly restricted to the surface and increases with the clay content, which has a positive influence over total porosity and a negative one over resistance to penetration. Soil density, maximum bulk density, available water, LLWR, and LLWR density equal to zero are negatively influenced by the clay content. Total porosity, optimal moisture content, field capacity, permanent wilting point, liquid and plastic limits, and plasticity index are positively influenced by the clay content. The ratio between optimal moisture content and plastic limit has a quadratic behavior in relation to clay content. The mean relative density corresponded to 0.86. LLWR decreased as clay and silt contents increased